Influence of demographic variables on job involvement of employees: a study in private banks in Tirupur - Kalpana, G.; Dharmaraj, A. (International Journal of Engineering and Technology, 2017)
Job involvement is generally described as an attachment to one's job that exceeds normal levels of commitment (Bhatia, A., et. al). The employee can become involved with his job which affects the performance in other life role areas. â€œThe degree to which an employee is engaged in and enthusiastic about performing their work is called Job Involvementâ€. Business managers are typically well aware that efforts to promote job involvement among staff tend to pay off substantially since employees will be more likely to assist in furthering their company's objectives. Job involvement is a degree to which an employee identifies with his job, actively participate in it, and consider his job performance important in his self-worth. It may be influenced by the level of oneâ€™s satisfaction of oneâ€™s need be their intrinsic or extrinsic. The objective of the study is to find out the level of job involvement of the bank employees and the factors influencing the job involvement of the bank employees. The findings of the study show that moderate level of job involvement has been found among the bank employees. The demographic factors namely age, gender, marital status, experience, salary do influence the level of job involvement of the bank employees.Â